Denigrate the reputation and its impact in dismantling the bonds of internal and societal peace in Islamic thought - Qadir Majid Husain Al-Qeshury (Zanco Journal of Humanity Sciences)
The human being carries with him a set of values ​​which he boasts of, including integrity, courage, honesty, honesty, social status, political position or job rank. He has the right to protect his reputation and dignity, and to defend them. He defends these values, and prevents distortion of the response to the distortion and false news. At the same time, the human is different in nature from one person to another, according to the social, educational and cultural environment in which they are educated, and some of them tend to discredit others for the purpose of themselves, Of the worst grade The person who does this may be due to events that have occurred, or that he carries a hatred or a heart attack which means reprisals by denigrating the reputation of those who want to, and there are also those who seek to belittle others and exclude them to be referred to as the best. This is because of the absence, slander, lying, misinformation, defamation, and slander which are considered to be major sins. God has assigned to each of them a certain punishment in the Holy Qur'an. God does not tolerate punishment of those who propagate bad propaganda without proof and proof. , Affected by internal and community peace, It is necessary to observe those who do not believe what they see of the work, or hear from the words, as you must try to bring them back to the right, while at the same time you must guide others to pay attention to their actions and words so as not to make room for them to think, all to maintain the bonds of peace and love between People brought to the interest and to deter the corrupt.